2019
DOI: 10.1103/physrevd.99.123519
|View full text |Cite
|
Sign up to set email alerts
|

Search for line-like signals in the all-sky Fermi-LAT data

Abstract: In order to search for the line-like signals in the Fermi-LAT data, we have analyzed totally 49152 regions of interest (ROIs) that cover the whole sky. No ROI displays a line signal with test statistic (TS) value above 25, while for 50 ROIs weak line-like excesses with TS > 16 are presented. The intrinsic significances of these potential signals are further reduced by the large trial factor introduced in such kind of analysis. For the largest TS value of 24.3 derived in our analysis, the corresponding global s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A search for such gamma-ray spectrum can be done from the H.E.S.S. and Fermi-LAT data [50,51]. Non-observation of such gamma ray emission from dwarf galaxies could serve as an evidence for this model.…”
Section: Discussionmentioning
confidence: 99%
“…A search for such gamma-ray spectrum can be done from the H.E.S.S. and Fermi-LAT data [50,51]. Non-observation of such gamma ray emission from dwarf galaxies could serve as an evidence for this model.…”
Section: Discussionmentioning
confidence: 99%
“…Great efforts have been paid to search for lines with Fermi Large Area Telescope (LAT) (Atwood et al 2009), but no significant signal has been found up to now (Abdo et al 2010;Vertongen & Weniger 2011;Ackermann et al 2012b;Bringmann et al 2012;Weniger 2012;Tempel et al 2012a;Su & Finkbeiner 2012a,b;Huang et al 2012b;Tempel et al 2012b;Ackermann et al 2013;Hektor et al 2013;Albert et al 2014;Ackermann et al 2015;Anderson et al 2016;Liang et al 2016a,b;Quincy Adams et al 2016;Liang et al 2017;Li et al 2019). Interestingly, some tentative lines have been reported above 3σ.…”
Section: Introductionmentioning
confidence: 99%
“…Another tentative line was found at ∼ 43 GeV in a GCls sample with a global significance of 3.0σ using 7.1-yr LAT P8R2 data (Liang et al 2016a). However, it does not appear in the Galactic center (Ackermann et al 2015), Milky Way satellites (Liang et al 2016b) and subhalos (Liang et al 2017;Li et al 2019). γ-ray line searches have also been performed with other telescopes such as DAMPE (Shen et al 2019), H.E.S.S.…”
Section: Introductionmentioning
confidence: 99%
“…The gamma-ray line above 10 GeV is one of the most important characteristic signals in the indirect detection of dark matter, as hardly any other astrophysical process can produce such kind of structure. Many works have been carried out on gamma-ray line search using the Fermi-LAT data, but only some tentative signals with low confidence are found so far [13][14][15][16][17][18], such as the line candidate found at about 43 GeV, which can also be interpreted as the product of annihilation of dark matter particles [19].…”
Section: Introductionmentioning
confidence: 99%